Reliability and Quality of Complex Systems - L.V. Loginova; A.A. Trofimov; E.A. Pecherskaya; I.M. Rybakov; N.A. Severtsev (Надежность и качество сложных систем)
Background. High-temperature semiconductor pressure sensors are used in many industries, including automotive, aerospace, aviation, and space. Aerospace systems require highly accurate and reliable sensors to measure various parameters, especially absolute pressure. Materials and methods. High-temperature semiconductor pressure sensors are one of the most effective solutions to these problems due to their high measurement accuracy, high resistance to external factors such as depressurization, depressurization, shock, vibration and temperature, as well as their use in harsh operating conditions, for example, when launching rockets into space. Results and conclusions. Creating a simulation model of a semiconductor absolute pressure sensor operating at high temperature for a space launch vehicle system is a necessary and important step in the development of a sensor converter. The development of touch sensors requires knowledge of the effect of real-world operating conditions on the sensor output characteristics at the design stage, without resorting to expensive physical tests.